Awareness of Factors Affecting Needle Stick Injuries Among Health Care Workers in the Operation Theatre of a Private Teaching Hospital of Lahore - Wajeeh Ur Rehman, Farwa Maheen, Mansab Ashfaq, Muhammad Umar Abbas, Fakhra Fakhr, Adeel Ahmed, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the knowledge, aptitude and practices of health care workers regarding needle stick injuries Material and methods: In this cross-sectional study, 109 healthcare works, serving in the Operation Theatre of Shalamar Hospital, Lahore participated. The data was entered and analyzed using SPSS 20. Chi-square test was used for the statistical analyses of the data. P-value of 0.05 or less was considered as significant Results: Among the healthcare professionals 55% were male and 45% were females. Among the subjects majority were doctors (42.2%). Most of the subjects have awareness (61.5%) regarding needles and sharp injuries. Though 45% had experienced needles and sharp injuries, only 18.3% reported the incident of needles and sharp injuries. 37.6% had strongly agreed that using gloves during the handling of needles and sharp objects can reduce the incidence of needles and sharp injuries while 11% disagreed. Similarly 59.6% strongly agreed that the presence of safety boxes at the workplace can reduce the incidence of needles and sharp injuries. Conclusion: By providing knowledge and proper guideline about prevention from needles and sharp injuries by using personal protective equipment, while handling contaminated blood and body fluids needles and sharp objects, can reduce the incidence of needles and sharp injuries. Keywords: Needle-Stick and Sharp Injuries, Operation Theatre, Health care workers